Supply Chain Sustainability in the Context of COVID-19 Pandemic in Pakistan’s Economy: Using Computable General Equilibrium (CGE) Model - Rasheed, Tuba; Shah, Zarwa; Subhan, Abdul; Rasheed, Aliya; Jadoon, Ume Tayyba; Khan, Muhammad Aamir (South Asian Journal of Social Sciences and Humanities, 2021)
The COVID 19 pandemic has had tremendous economic impacts and continues to wreak havoc around the world. This research work has been conducted to analyze the macroeconomic effects of the COVID 19 in the context of Pakistan. The impact ECON Supply Chain (IESC) Computable general equilibrium (CGE) Model which was formulated by Walmsley and Minor (2016) has been employed so that the supply chain effects of many of Pakistan’s government policies in response to the coronavirus pandemic can be assessed. An 8% shock was given to 11 sectors of the economy and a 5% shock was given to electricity. Lastly, the impact of these shocks on all 31 sectors of the economy that are included in the model was assessed. Results discovered that there was a decline in real GDP, real exports, real imports, and per capita utility from private expenditure, meanwhile, terms of trade and regional household income increased. This study also illuminated that during pandemic goods market prices increased for 16 sectors while supply price of commodities decreased for 15 sectors. Based on the empirical findings, some relevant policy implications are suggested to overcome the pandemic.
Keywords: COVID 19 Pandemic; Supply Chain; Economic Losses; Computable General Equilibrium Model; Pakistan